A comparative study of aligned and random electrospun mats of thermoplastic polyurethane and conductive additives based on polypyrrole. (September 2018) - Merlini, Claudia; Silveira, Adriana; Ramôa, Sílvia D.A.S.; Soares, Bluma G.; Alavarse, Alex Carvalho; Bonvent, Jean-Jacques; Barra, Guilherme M.O.
Abstract: Non-woven mats of thermoplastic polyurethane (TPU) with montmorillonite-dodecylbenzenesulfonic acid-doped polypyrrole (MMT-PPy.DBSA) and dodecylbenzenesulfonic acid-doped polypyrrole (PPy.DBSA) were prepared by electrospinning using both a stationary and rotating collector. The effect of MMT-PPy.DBSA and PPy.DBSA content on the properties of TPU solution, mat morphology, and mechanical and electrical properties was investigated. The morphology, fiber diameter, mechanical properties and electrical conductivity of the mats were influenced by the collector and filler type. The TPU/MMT-PPy.DBSA mats exhibited more uniform fibers, and higher mechanical properties and electrical conductivity than found for TPU/PPy.DBSA. In order to investigate the feasibility and potential applications of TPU/MMT.PPy.DBSA and TPU/PPy.DBSA mats in biomedical applications, preliminary tests of cell viability were performed. The cytotoxicity of electrospun mats was influenced by the type and amount of conductive filler, where TPU and TPU/PPy.DBSA mats showed higher than 100% viability after 48 h of incubation. On the other hand, cell viability for TPU/MMT.PPy.DBSA mats was observed only for low filler concentration (5 wt%). Graphical abstract: Image 1